Softer soju in South Korea. (March 2013) - Harkness, Nicholas
This paper explores the ascendancy of 'softness' in South Korea as it is experienced through the qualia of one of Korea's most important social rituals: drinking soju. I combine an analysis of ethnographic evidence with widely-distributed advertisements to show how the experience of an abstract quality, softness, is made concrete by the cultural-semiotic renderings – and genderings – of alcohol consumption in various sensory modalities, including gustation, audition, kinaesthesis, and states of overall drunkenness. I introduce the concept of 'qualic transitivity' to account for the cross-modal perception of qualia as instances of the same quality. I argue that dramatic shifts in the qualia of soju and its consumption are emblematic of a higher-order change in how the ideal relationship between liquor and gender is being reconceptualized in contemporary South Korean society.